Cinema encruzilhada: as performances culturais e o campo do filme documentário - Gama, Alessandra Regina (2022)
In this work we are interested in investigating, in the light of cultural performances, ways of representations of the Afro-Brazilian cosmovision, in documentary films that contribute to aesthetic and political reflections about representational practices of Candomblé and Afro-diasporic cultures. In this context, similarity, difference and otherness, therefore, identity issues, are mixed with symptoms historical racial groups that sediment representational practices of stereotyping. We start from the assumption that the points of contact between the performances cultural and documentary, crossed by the Afro-Brazilian cosmovision, configure an aesthetics of the crossroads and, thus, articulate codes, texts, gestures and symbolic systems, which create meanings and, consequently, elaborate responses to representational practices. To address the problem presented, we started the theoretical reflections approaching the relations between cultural performances and the field of documentary film from the crossroads perspective, which highlights the epistemic linkage of behaviors and narratives coherently aesthetic and policies, based on the perspective of the Afro-diasporic cosmovision. The studies on representational policies help us to think about the power embedded in the notion of representation as a creative act that challenges stereotypes through counter-strategic intervention and inversion movements. We are interested in establishing an opposing view of the colonialist discourse from which the historical and cultural formation of the peoples of the West derives. To that end, we invest in studies by authors of the main reference bases: Leda Maria Martins, Diana Taylor, Richard Schechner, Victor Turner, Fernão Ramos, Bill Nichols, Stela Bruzzi, Cláudio Bezerra, Manuela Penafria, bell hooks, Robert Stam, Stuart Hall, Beatriz Nascimento and Muniz Sodré. From the articulation invested in the notion of cinema crossroads, we move on to the filmic analysis of the documentary series carried out by the Society for the Study of Black Culture in Brazil – SECNEB: Orixá Ninu Ilê (1978), Iyá-Mi-Agbá (1981) and Egungun (1982). The result is an analysis of images and sounds that compose a cinematography interested in the dispute of modes of representation, based on the proposition of a decolonized look about the images and sounds of Afrodiasporic cultural performances.